2021
DOI: 10.1108/ijchm-03-2021-0323
|View full text |Cite
|
Sign up to set email alerts
|

Empowering leadership in hospitality and tourism management: a systematic literature review

Abstract: Purpose This study aims to review the empirical studies on empowering leadership in hospitality and tourism and proposes an associated research agenda. Design/methodology/approach A disciplined selection process using transparent inclusion and exclusion criteria resulted in a final sample of 25 empirical studies. The research results from these studies were systematically analyzed using content analysis. Findings The synthesis of these articles highlights that: studies on empowering leadership in hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 95 publications
(172 reference statements)
6
74
0
Order By: Relevance
“…These results are compatible with Arici et al (2021), who found a cluster on empowerment located in the center of the network and connected to the other clusters, even though it contained only a few studies. In analyzing our results in the empowering leadership cluster, we agree with Hoang et al (2021) that the focus on psychological outcomes (psychological empowerment, job autonomy, psychological contract fulfilment, self-efficacy) dominates at the individual level. This prevalence explains why self-determination theory and social learning theory are commonly used to study how empowering leaders foster service performance.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These results are compatible with Arici et al (2021), who found a cluster on empowerment located in the center of the network and connected to the other clusters, even though it contained only a few studies. In analyzing our results in the empowering leadership cluster, we agree with Hoang et al (2021) that the focus on psychological outcomes (psychological empowerment, job autonomy, psychological contract fulfilment, self-efficacy) dominates at the individual level. This prevalence explains why self-determination theory and social learning theory are commonly used to study how empowering leaders foster service performance.…”
Section: Discussionsupporting
confidence: 80%
“…As in leadership research in the general management literature, we note the predominance of theoretical frameworks borrowed from psychology and sociology (such as COR theory, social exchange theory and social learning theory) to explain leadership phenomena in hospitality (Bavik, 2020; Eva et al , 2019; Hoang et al , 2021). This similarity can be explained by the focus on leadership’s consequences at employee level in terms of attitudes, behaviors and performance (job satisfaction, organizational commitment, turnover, OCB, engagement, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior systematic reviews focused on the review of leadership in specific countries, such as Spain (Bark et al, 2014). Our review draws on recommendations from literature, Bavik (2020), Chon and Zoltan (2019) and Hoang et al (2021), who call for more reviews on leadership in hospitality and tourism to understand theoretical frameworks, antecedents and consequences. In their review, Gui et al (2021) affirmed that there is a need to conduct a review on leadership styles such as SEL because few scholars have quantified the findings of multiple studies and presented a quantitative approximation of the relationship between SEL and follower achievements in the hotel industry.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no systematic literature review for leadership styles research in hospitality including hotels, restaurants, resorts, motels, casinos, nightclubs and food service operations. Prior systematic reviews have addressed other IJCHM 34,5 disciplines, such as nursing (Cummings et al, 2008;Wong and Cummings, 2007) and with reviews mostly focusing on one leadership style, such as empowering leadership in hospitality and tourism management (Hoang et al, 2021) and SEL (Eva et al, 2019), especially in hospitality management (Bavik, 2020;Chon and Zoltan, 2019).…”
Section: Introductionmentioning
confidence: 99%